2018
DOI: 10.3389/fphys.2018.01595
|View full text |Cite
|
Sign up to set email alerts
|

Heme Induces Endoplasmic Reticulum Stress (HIER Stress) in Human Aortic Smooth Muscle Cells

Abstract: Accumulation of damaged or misfolded proteins resulted from oxidative protein modification induces endoplasmic reticulum (ER) stress by activating the pathways of unfolded protein response. In pathologic hemolytic conditions, extracellular free hemoglobin is submitted to rapid oxidation causing heme release. Resident cells of atherosclerotic lesions, after intraplaque hemorrhage, are exposed to heme leading to oxidative injury. Therefore, we raised the question whether heme can also provoke ER stress. Smooth m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 139 publications
(193 reference statements)
0
29
0
Order By: Relevance
“…In addition, there is substitution A>T at position −27 of the HBB promoter (hereinafter: HBB:−27A>T) [80] (not covered by either the "1000 Genomes" project [10] or dbSNP [12]), which causes HBB overexpression that has been clinically associated with the norm of the two above-mentioned biomedical traits [80] (Table 3). Nonetheless, our keyword search via PubMed [38] led to a clinical research article [81] on the heme released by extracellular HBB (after hemolysis), as an accelerator of atherogenesis. That is why we predicted that the known SNP marker HBB:−27A>T of the norm of both malaria resistance and thalassemia [80] can also be a candidate SNP marker of accelerated atherogenesis (Table 3).…”
Section: Human Genes Associated With Blood Disordersmentioning
confidence: 99%
“…In addition, there is substitution A>T at position −27 of the HBB promoter (hereinafter: HBB:−27A>T) [80] (not covered by either the "1000 Genomes" project [10] or dbSNP [12]), which causes HBB overexpression that has been clinically associated with the norm of the two above-mentioned biomedical traits [80] (Table 3). Nonetheless, our keyword search via PubMed [38] led to a clinical research article [81] on the heme released by extracellular HBB (after hemolysis), as an accelerator of atherogenesis. That is why we predicted that the known SNP marker HBB:−27A>T of the norm of both malaria resistance and thalassemia [80] can also be a candidate SNP marker of accelerated atherogenesis (Table 3).…”
Section: Human Genes Associated With Blood Disordersmentioning
confidence: 99%
“…Another important finding was that heme could potentially cause endothelial cell dysfunction via increased iron-mediated ROS [124]. Recent research also showed that free heme in cells could trigger endoplasmic reticulum (ER) stress [125] that was also found in patients with PAH [126]. Treating rodents with the chemical chaperone phenyl-butyric acid alleviated ER stress and reduced symptoms of PAH induced by hypoxia [127], indicating that free heme could initiate PAH through ER stress.…”
Section: Sources Of Ros In Pah and The Role Of Gendermentioning
confidence: 99%
“…UPR compensates stress maintaining cellular homeostasis and avoiding cell death. Heme induces ER stress by expression of activating transcription factor-4 (ATF4) as well as splicing of X-box binding protein-1 (XBP1), promoting upregulation of targets such as CHOP (C/EBP homology protein) (Gall et al, 2018). Administration of transferrin, hemopexin, and haptoglobin resulted in beneficial extravascular/intravascular hemolytic anemias (Buehler and Karnaukhova, 2018).…”
Section: Introductionmentioning
confidence: 99%